Friday Noraebang's Marketing PR Strategies Shape Brand Image Through Powerful Collaboration - Pinariya, Janette Maria; Ramadhani, Rifa; Fadel, Mohamad (Journal of Research on Business and Tourism, 2025)
Korean culture has been a global trend for over thirty years, influencing the world. The Korean entertainment industry has grown rapidly, called the Hallyu phenomenon. Indonesia has a large Hallyu market, providing a golden opportunity for businesses like Friday Noraebang’s, a karaoke event organizer. This research aims to understand and to analyse Friday Noraebang’s Marketing Public Relations strategy to develop a positive image, by collaborating with other brands, and to identify obstacles and solutions to this strategy. It uses Marketing Public Relations approaches such as the pull, push, and pass strategies, with the PESO model concept. The research methodology used is descriptive qualitative method with interview techniques and secondary data. This research found that Friday Noraebang’s has successfully implemented three Marketing Public Relations strategies based on factors that form brand image and six elements of co-branding. The pull, push and pass strategy approach, as well as the use of social media and co-branding collaboration, are the keys to Friday Noraebang’s success in building and strengthening its brand image. Brand that have survived the pandemic are able to adapt to changes in promotional styles, maximising their flexibility and creativity to maintain audience engagement competitive advantage in the entertainment industry.